Acute Budd-Chiari Syndrome with Complete Portal Vein Thrombosis Complicated by Hepato-Renal Syndrome Treated Successfully by Emergent TIPS with Rheolytic Thrombectomy - Michieletti, Emanuele; Bodini, Flavio C.; Morelli, Nicola; Rossi, Beatrice; Bossalini, Margherita; Colombi, Davide (Journal of clinical and experimental hepatology, 2023)
We described a case of a 73-year-old female admitted to the emergency department with acute hepatic and renal failure (hepato-renal syndrome, HRS) due to acute Budd-Chiari syndrome associated with complete portal vein thrombosis (BCS-PVT) for an unknown cause. Despite the initial therapy with anticoagulants, a sudden impairment of the renal function requiring hemodialysis was observed. The hepatic transplant was excluded for patient age and clinical conditions. Thus, the patient was successfully treated by emergent transjugular intrahepatic portosystemic shunt (TIPS) previous rheolytic thrombectomy of the PVT with AngioJet Ultra PE Thrombectomy System (Boston Scientific, Marlborough, MA, USA). After the procedure, the sudden resolution of the HRS was observed, and the patient is alive 13 months after hospital dismission with no TIPS dysfunction. In conclusion, emergent extended TIPS with the usage of rheolytic thrombectomy device in patient with acute BCS-PVT complicated by HRS is feasible by experienced operators and provide resolution of the HRS.